Plan de Marketing de Posicionamiento de marca en la empresa DK Asesores de la ciudad de Loja - Tamayo Jiménez, Kleber Patricio (2024)
The present investigation seeks the growth of the company DK Asesores against its competitors, having as general objective to elaborate a marketing plan of brand positioning in the company DK Asesores of the city of Loja, with the purpose of improving the growth of the company. Establishing the following objectives: First, to make a situational diagnosis of the company DK Asesores in the city of Loja, leaving a negative result since it does not have an integrated business philosophy, to develop a market study to determine the positioning that the company has, thus giving that it does not have a good positioning since it is one of the least known compared to its competitors, in addition to 48% of customers do not recognize the brand. Develop a marketing plan for brand positioning for the company, in which it was determined that it is necessary to develop a branding of the brand to improve the positioning adding that it is essential to invest in advertising to improve its visibility in the market, for which three strategic objectives were developed as the development of the business philosophy: mission, vision and business values, the development of a branding of the visual identity of the brand, logo, slogan and improve digital advertising on social networks within the market. In order to respond to this, we proceeded to use research methods such as the exploratory to determine the problem and the descriptive to describe the characteristics and desires of the group of interest, for the study we determined a random sample of 398 potential customers and 222 real customers of the Lojana population, using instruments such as observation, surveys and interviews, it was recommended that the new logo should be disseminated massively and evaluate the effectiveness of the changes.